Formas de vida da mulher brasileira no discurso jurídico - Prestes, Cleides Maria Silva [UNESP] (2015)
Assuming that French semiotics allows the analyzis of several languages and textual genres, women's ways of life were sought to be verified in the legal discourse, in the main Brazilian laws related to women, from some articles belonging to the Civil Code of 1916 to the advent of the Law 11340, known as Maria da Penha Law, which was published on August 7th, 2006. For this reason, considerations about the relationship between semiotics and law were made, since legal texts were considered to belong to the legislative field, according to E. Landowski's studies on socio-semiotics. Also, it was considered that the advent of a law is an event that somehow, or at least in a collective and a potential way, breaks a routine, for all citizens usually must know and obey the current laws of their county. It is believed that it is possible to demonstrate semiotic practices and stereotypes manifested in each legal text with regard to women's ways of life. From this premise, two questions emerge: how does the legal discourse in the form of laws reflect these practices? Through what enunciation strategies does it occur? In order to answer these questions, the postulates of French semiotics, mainly those related to A. J. Greimas' studies, the foundations of legal semiotics and J. Fontanille's, C. Zilberberg's and E. Landowski's latest postulates about ways of life, were applied. Finally, the architecture of legal texts was sought to be revealed. These texts were considered an event that breaks a routine and proposes new semiotic practices, habits, language games, i.e. ways of life, which imply the denial or referendum of previous practices concerning women. In a broader sense, it is a study related to semiotics of cultures, according to greimasian conception